Xanthohumol Requires the Intestinal Microbiota to Improve Glucose Metabolism in Diet‐Induced Obese Mice. Issue 21 (12th October 2021) - Logan, Isabelle E.; Shulzhenko, Natalia; Sharpton, Thomas J.; Bobe, Gerd; Liu, Kitty; Nuss, Stephanie; Jones, Megan L.; Miranda, Cristobal L.; Vasquez‐Perez, Stephany; Pennington, Jamie M.; Leonard, Scott W.; Choi, Jaewoo; et al.
Abstract : Scope: The polyphenol xanthohumol (XN) improves dysfunctional glucose and lipid metabolism in diet‐induced obesity animal models. Because XN changes intestinal microbiota composition, the study hypothesizes that XN requires the microbiota to mediate its benefits. Methods and Results: To test the hypothesis, the study feeds conventional and germ‐free male Swiss Webster mice either a low‐fat diet (LFD, 10% fat derived calories), a high‐fat diet (HFD, 60% fat derived calories), or a high‐fat diet supplemented with XN at 60 mg kg −1 body weight per day (HXN) for 10 weeks, and measure parameters of glucose and lipid metabolism. In conventional mice, the study discovers XN supplementation decreases plasma insulin concentrations and improves Homeostatic Model Assessment of Insulin Resistance (HOMA‐IR). In germ‐free mice, XN supplementation fails to improve these outcomes. Fecal sample 16S rRNA gene sequencing analysis suggests XN supplementation changes microbial composition and dramatically alters the predicted functional capacity of the intestinal microbiota. Furthermore, the intestinal microbiota metabolizes XN into bioactive compounds, including dihydroxanthohumol (DXN), an anti‐obesogenic compound with improved bioavailability. Conclusion: XN requires the intestinal microbiota to mediate its benefits, which involves complex diet‐host‐microbiota interactions with changes in both microbial composition and functional capacity. The study results warrant future metagenomic studies which will provide insight into complex microbe‐microbe interactions and diet‐host‐microbiota interactions. Abstract : The hops polyphenol xanthohumol (XN) improves dysfunctional glucose metabolism in mouse models of diet‐induced obesity concomitant with changes in the gut microbiota and its predicted functional capacity. In a germ‐free mouse model of diet‐induced obesity, XN supplementation failed to improve glucose metabolism compared with conventional mice. These findings suggest the intestinal microbiota are required for mediating benefits of XN.